Differences among three wheat cultivars in susceptibility to Fusarium culmorum and the effect of a number of bacterial strains on infested seed germination - Tahsein A. M. Amein (Zanco Journal of Pure and Applied Sciences, 2023)
Wheat seedling blight caused by Fusarium culmorum, is one of the most common among wheat diseases. Last decades, use of resistant cultivars and biological control by antagonistic micro-organisms have received much attention. Resistance levels of three wheat cultivars (Saber Bag, Smito and Sham 5) to this disease was assessed under greenhouse conditions. None of the cultivars was high resistant but Saber Bag showed the highest germination rate 63.3%. This was 11% more than the two other cultivars. In a dual culture three bacterial strains, two Bacillus and one Pseudomonas had very good effect in inhibition of the mycelium growth of this fungus. Bacterial strain Bacillus sp M1, B. subtilis K3 and Pseudomonas sp 53 inhibited the fungal mycelium growth by 100%, 97.5 %, and 98% respectively. In greenhouse experiments, bacterial strain M1 increased the number of seed germinations by 50% compared to untreated Fusarium control in cv. Sham5 and 43% in cv. Smito. Also strain 53 increased the number of germinations by 35% in cv. Smito.